2014
DOI: 10.1242/jcs.154922
|View full text |Cite
|
Sign up to set email alerts
|

CDK2 regulates nuclear envelope protein dynamics and telomere attachment in mouse meiotic prophase

Abstract: In most organisms, telomeres attach to the nuclear envelope at the onset of meiosis to promote the crucial processes of pairing, recombination and synapsis during prophase I. This attachment of meiotic telomeres is mediated by the specific distribution of several nuclear envelope components that interact with the attachment plates of the synaptonemal complex. We have determined by immunofluorescence and electron microscopy that the ablation of the kinase CDK2 alters the nuclear envelope in mouse spermatocytes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
71
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(79 citation statements)
references
References 46 publications
7
71
0
1
Order By: Relevance
“…A similar defect has been described in CDK2 null spermatocytes (Viera et al 2015). These cells exhibited alterations in the nuclear envelope and detached telomeres in the nuclear space that were associated with the LINC complex protein SUN1 and with residual NE proteins (Viera et al 2015). We previously reported that both cyclin E1 and E2 interact with CDK2 and drive its localization in telomeres during pachynema and diplonema.…”
Section: Resultssupporting
confidence: 78%
“…A similar defect has been described in CDK2 null spermatocytes (Viera et al 2015). These cells exhibited alterations in the nuclear envelope and detached telomeres in the nuclear space that were associated with the LINC complex protein SUN1 and with residual NE proteins (Viera et al 2015). We previously reported that both cyclin E1 and E2 interact with CDK2 and drive its localization in telomeres during pachynema and diplonema.…”
Section: Resultssupporting
confidence: 78%
“…The kinase activity of Cdk2 on telomeres can be activated by Speedy A, but it is likely that other cyclins also activate the telomeric Cdk2, which in turn regulates telomere-led chromosome movements on the NE, possibly through phosphorylation of SUN1 (19,34). It has been reported that E-type cyclins (E1 and E2) also form complexes with Cdk2 in mouse spermatocytes, and the knockout mice for Ccne1 and Ccne2 partially mimic the phenotypes seen in Cdk2 −/− spermatocytes, suggesting the involvement of canonical cyclins in the activation of Cdk2 during meiosis (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Telomere attachment to SUN1 is regulated by phosphorylation of the SUN1 N-terminal domain in both mouse (Ortega et al, 2003; Viera et al, 2015; Viera et al, 2009) and in C. elegans (Penkner et al, 2009). SUN1 phosphorylation is induced in mice by the Cyclin-dependent kinase, Cdk2.…”
Section: The Zygotene Chromosomal Bouquetmentioning
confidence: 99%
“…SUN1 phosphorylation is induced in mice by the Cyclin-dependent kinase, Cdk2. cdk2 −/− mice are viable, but sterile, and in mutant spermatocytes and oocytes, telomeres do not localize to SUN1 on the NE and synapsis is abrogated (Ortega et al, 2003; Viera et al, 2015; Viera et al, 2009). Importantly, Cdk2 purified from testes was shown to phosphorylate the N-terminus of SUN1 in vitro (Viera et al, 2015).…”
Section: The Zygotene Chromosomal Bouquetmentioning
confidence: 99%